Approximation by Modified Lupaş-Stancu Operators Based on (p, q)-Integers - Khan, Asif; Abbas, Zaheer; Qasim, Mohd; Mursaleen, Mohammad (Eurasian Mathematical Journal, 2021)
The purpose of this paper is to construct a new class of Lupaş operators in the frame of post quantum setting. We obtain a Korovkin type approximation theorem, study the rate of convergence of these operators by using the concept of the K-functional and modulus of continuity, also give a convergence theorem for the Lipschitz continuous functions.